The construction of China-ASEAN Zhuang and Thai language culture converged community in the context of the belt and road initiative - Long, Bai; Liheng, Hok; Kim Phuong, Luong (Universitas Ahmad Dahlan, 2023)
Thailand,other Belt and Road country, exists linguistic phenomenon that its official Language which is Thai language and Zhuang language are on the isogeny and dissimilation. With a history behind Zhuang and Thai language,historic culture of Bai Yue ancestors are traced to the same origin. The relevance of two languages and culture of identical source need to be further studied. Zhuang and Thai language consensus in the cultural field is cultural practice of community with shared future for mankind consciousness. Transnational cultural blend maintain the minority culture vitality and extend potential influence of Zhuang and Thai language. Two countries,therefore, comply with the Belt and Road Initiative constructing Zhuang and Thai language culture community. Tracing back historical memories of nation and creating integration of language and culture are striven for greatest common cooperation in order to promote a sense of community between Zhuang and Thai nations and protect unique language culture symbol of Zhuang and Thai nations. Only in this way can the discourse power of Zhuang Language promote under expansively continuous transnational horizon, cultural transmission and dialogues among civilizations speed up and Chinese stories of Zhuang tell excellently.